Improving T-DNA Transfer to Tamarix hispida by Adding Chemical Compounds During Agrobacterium tumefaciens Culture - Zhao, Huimin; Jia, Yaqi; Cao, Yanting; Wang, Yucheng (Frontiers in Plant Science, 2020)
ABSTRACT Agrobacterium tumefaciens-mediated gene transfer is the most commonly used method for plant genetic engineering. However, during the period of A. tumefaciens culture, the effects of Agrobacterium culture before inoculation on genetic transformation are poorly understood. In the present study, we investigated the factors that affect the genetic transformation efficiency during Agrobacterium culture using Tamarix hispida as transgenic plant material. Agrobacterium treatment with spermidine (Spe), azacitidine (5-AzaC), dithiothreitol (DTT), or acetosyringone (AS) alone all significantly improved the efficiency of T-DNA transfer. Treatment with 5-AzaC reduced DNA methylation in Agrobacterium to induce the expression of virulence (vir) family genes, including virA, virB1, virC1, virD2, virD4 virE2, and virG. Spe treatment significantly induced the expression of all the studied genes, including virA, virB1, virC1, virD1, virD2, virD4, virE2, and virG. DTT treatment decreased reactive oxygen species accumulation. AS treatment activated the expression of the genes virA, virB1, virC1, virD1, virD2, virD4 and virG. All these effects resulted in increased T-DNA transfer. Additionally, combined Spe, 5-AzaC, DTT, and AS treatment improve Agrobacterium infection to a greater extent compared with their use alone, increasing T-DNA transfer by more than 8-fold relative to no treatment. Therefore, to improve genetic transformation, pretreatment of Agrobacterium during the culture period is important for improving genetic transformation efficiency.